Efficacy and safety of immunosuppressive agents for adults with lupus nephritis: a systematic review and network meta-analysis - Jiang, Nan; Jin, Shangyi; Yu, Chen; Zhao, Jiuliang; Wang, Qian; Tian, Xinping; Li, Mengtao; Zeng, Xiaofeng (Frontiers in Immunology, 2023)
Various immunosuppressive regimens have been developed for the treatment of lupus nephritis (LN). This study aimed to compare the efficacy and safety of immunosuppressive regimens in adults with LN. We systematically searched the PubMed, Embase, and Cochrane Central Register of Controlled Trials databases, including conference proceedings, trial registries, and reference lists, from inception until July 10, 2022. The effects of treatment were compared and ranked using the surface under the cumulative ranking curve (SUCRA). The primary endpoint was total remission. The secondary endpoints were complete remission, systemic lupus erythematosus disease activity index (SLEDAI), relapse, all-cause mortality, end-stage renal disease (ESRD), infection, herpes zoster, ovarian failure, myelosuppression, and cancer. Sixty-two trials reported in 172 studies involving 6,936 patients were included in the network meta-analysis. The combination of tacrolimus (TAC), mycophenolate mofetil (MMF), and glucocorticoid (GC) provided the best result for the total remission rate (SUCRA, 86.63%) and SLEDAI (SUCRA, 91.00%), while the combination of voclosporin, (VCS) , MMF and GC gave the best improvement in the complete remission rate (SUCRA, 90.71%). The combination of cyclophosphamide (CYC), MMF and GC was associated with the lowest risk of relapse (SUCRA, 85.57%) and cancer (SUCRA, 85.14%), while the combination of obinutuzumab (OTB), MMF and GC was associated with the lowest risk of all-cause mortality (SUCRA, 84.07%). Rituximab (RTX) plus MMF plus GC was associated with the lowest risk of ESRD (SUCRA, 83.11%), while the risk of infection was lowest in patients treated with azathioprine (AZA) plus CYC plus GC (SUCRA, 68.59%). TAC plus GC was associated with the lowest risk of herpes zoster (SUCRA, 87.67%) and ovarian failure (SUCRA, 73.60%). Cyclosporine (CsA) plus GC was associated with the lowest risk of myelosuppression (SUCRA, 79.50%), while AZA plus GC was associated with the highest risk of myelosuppression (SUCRA, 16.25%). This study showed that a combination of TAC, MMF and GC was the best regimen for improving the total remission rate. The optimal regimen for specific outcomes should be highlighted for high-risk patients.